SISTEM INFORMASI INVENTARIS BARANG BERBASIS WEB PADA DINAS KOMUNIKASI DAN INFORMASI BONDOWOSO - Lutfiana , Nurisma; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
The Web-Based Inventory Information System at the Bondowoso Communication and Information Service aims to improve efficiency and accuracy in asset management. In the context of government, effective inventory management is essential to ensure transparency and accountability in resource use. This study began with a needs analysis through interviews and surveys of users, which was then followed by system design using flowcharts and Data Flow Diagrams (DFD). The developed system integrates the process of inputting, maintaining, and reporting inventory, and provides a user-friendly interface. The software development methodology used is waterfall, which allows adjustments based on user feedback during the testing phase. The implementation results show that the system is able to reduce data errors, accelerate the decision-making process, and improve collaboration between departments within the service. Thus, this Web-Based Inventory Information System not only meets administrative needs but also contributes to better asset management at the Bondowoso Communication and Information Service. This study is expected to be a reference for other government agencies in implementing similar systems to improve the efficiency and transparency of inventory management.